2011
DOI: 10.1128/mcb.00734-10
|View full text |Cite
|
Sign up to set email alerts
|

The Rhox Homeobox Gene Cluster Is Imprinted and Selectively Targeted for Regulation by Histone H1 and DNA Methylation

Abstract: Histone H1 is an abundant and essential component of chromatin whose precise role in regulating gene expression is poorly understood. Here, we report that a major target of H1-mediated regulation in embryonic stem (ES) cells is the X-linked Rhox homeobox gene cluster. To address the underlying mechanism, we examined the founding member of the Rhox gene cluster-Rhox5-and found that its distal promoter (Pd) loses H1, undergoes demethylation, and is transcriptionally activated in response to loss of H1 genes in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 61 publications
4
51
0
Order By: Relevance
“…ES cells have been increasingly employed as a model system for studying genomic imprinting (9,25,(42)(43)(44)(45)(46). Indeed, we found that ZFP57 maintains DNA methylation imprint at a large subset of imprinted regions in ES cells.…”
mentioning
confidence: 64%
“…ES cells have been increasingly employed as a model system for studying genomic imprinting (9,25,(42)(43)(44)(45)(46). Indeed, we found that ZFP57 maintains DNA methylation imprint at a large subset of imprinted regions in ES cells.…”
mentioning
confidence: 64%
“…Interestingly, genes known to escape XCI, such as Kdm5c, escaped XCI in X JF1 /X 129 Xist1Lox;GFP TS cells in a reciprocal pattern to that of X JF1 /X 129 Xist2Lox;GFP TS cells. Genes known to be imprinted in adult tissues, such as Rhox6 (Maclean et al, 2011), followed the patterns of genes subject to imprinted XCI. It should be noted that when Cre-expressing constructs were introduced into X JF1 /X 129 Xist2Lox;GFP TS cells, we were unable to recover X JF1 /X 129 Xist1Lox;GFP TS cells, whereas the same Cre constructs introduced into X/X Xist2Lox embryonic stem (ES) cells produced X/X Xist1Lox ES colonies.…”
Section: Research Articlementioning
confidence: 99%
“…This is further supported by studies examining RHOX regulation. Both mouse and human RHOX family members have been demonstrated to be strongly regulated by DNA methylation (25)(26)(27) and there is an association between RHOX hypermethylation and abnormal sperm in idiopathic infertile patients (14).…”
mentioning
confidence: 99%